Collaboration between Nahdlatul Ulama and Higher Education in Improving the Quality of Islamic Education in Indonesia - Siregar, Rahmad Ramadhan; Guntara, Peter; Effendi, Irwan (LAKPESDAM MWCNU Palengaan, 2025)
This research is a descriptive qualitative study that discusses collaboration and strategies to improve the quality of higher education managed by Nahdlatul Ulama (NU) with the New Institutionalism theory approach as an analytical framework. NU as the largest socio-religious organisation in Indonesia has developed a higher education model that integrates pesantren tradition, moderate Islamic science, and an institutional approach (LPTNU) that is adaptive to the challenges of the times. Innovative strategies in the form of integration of keulamaan research and global santri academic networks are designed to strengthen academic capacity, expand international collaboration, and promote Islamic values in the global academic space. The results of this study show that the synergy between institutional foundation, value-based strategy and international cooperation is a strategic combination in creating a sustainable, competitive and socially relevant transformation of Islamic higher education. Penelitian ini bersifat kualitatif deskriptif yang membahas kolaborasi dan strategi peningkatan kualitas pendidikan tinggi yang dikelola oleh Nahdlatul Ulama (NU). NU sebagai organisasi sosial-keagamaan terbesar di Indonesia telah mengembangkan model pendidikan tinggi yang mengintegrasikan tradisi pesantren, keilmuan Islam moderat, dan pendekatan kelembagaan (LPTNU) yang adaptif terhadap tantangan zaman. Strategi inovatif berupa integrasi riset keulamaan dan jejaring akademik santri global yang dirancang untuk memperkuat kapasitas akademik, memperluas kolaborasi internasional, serta mempromosikan nilai-nilai Islam dalam ruang akademik global. Hasil dari penelitian ini menunjukkan bahwa sinergi antara landasan institusional, strategi berbasis nilai dan kerja sama internasional merupakan kombinasi strategis dalam menciptakan transformasi pendidikan tinggi Islam yang berkelanjutan, berdaya saing, dan relevan secara sosial.